Environmental toxicant induced epigenetic transgenerational inheritance of ovarian pathology and granulosa cell epigenome and transcriptome alterations: ancestral origins of polycystic ovarian syndrome and primary ovarian insufficiency. Issue 8 (3rd August 2018) - Nilsson, Eric; Klukovich, Rachel; Sadler-Riggleman, Ingrid; Beck, Daniel; Xie, Yeming; Yan, Wei; Skinner, Michael K.
ABSTRACT: Two of the most prevalent ovarian diseases affecting women's fertility and health are Primary Ovarian Insufficiency (POI) and Polycystic Ovarian Syndrome (PCOS). Previous studies have shown that exposure to a number of environmental toxicants can promote the epigenetic transgenerational inheritance of ovarian disease. In the current study, transgenerational changes to the transcriptome and epigenome of ovarian granulosa cells are characterized in F3 generation rats after ancestral vinclozolin or DDT exposures. In purified granulosa cells from 20-day-old F3 generation females, 164 differentially methylated regions (DMRs) ( P  < 1 x 10 −6 ) were found in the F3 generation vinclozolin lineage and 293 DMRs ( P  < 1 x 10 −6 ) in the DDT lineage, compared to controls. Long noncoding RNAs (lncRNAs) and small noncoding RNAs (sncRNAs) were found to be differentially expressed in both the vinclozolin and DDT lineage granulosa cells. There were 492 sncRNAs ( P  < 1 x 10 −4 ) in the vinclozolin lineage and 1, 085 sncRNAs ( P  < 1 x 10 −4 ) in the DDT lineage. There were 123 lncRNAs and 51 lncRNAs in the vinclozolin and DDT lineages, respectively ( P  < 1 x 10 −4 ). Differentially expressed mRNAs were also found in the vinclozolin lineage (174 mRNAs at P  < 1 x 10 −4 ) and the DDT lineage (212 mRNAs at P  < 1 x 10 −4 ) granulosa cells. Comparisons with known ovarian disease associated genes were made. These transgenerational epigenetic changes appear to contribute to the dysregulation of the ovary and disease susceptibility that can occur in later life. Observations suggest that ancestral exposure to toxicants is a risk factor that must be considered in the molecular etiology of ovarian disease.